2015
DOI: 10.4103/0366-6999.164869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Left Ventricular Thrombus after Acute Myocardial Infarction

Abstract: Background:Left ventricular thrombus (LVT) is reported to be a common complication in acute myocardial infarction (AMI) patients. And it has the potential to cause systemic embolism. This retrospective study was to present the current situation of LVT in clinical practice, as well as to evaluate the clinical characteristics and the risk factors of LVT after AMI.Methods:LVT cases (n = 96) were identified from 13,732 AMI (non-ST elevation myocardial infarction was excluded) patients in Fuwai Hospital's electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Regrettably, there was no statistical significance after multivariate analysis. Moreover, consistent with prior studies [27,28], we also demonstrated an independent association between left ventricular aneurysm and LVT. Interestingly, sixteen patients were diagnosed with ventricular aneurysm, 93.75% (15/16) of whom had LVT.…”
Section: Discussionsupporting
confidence: 92%
“…Regrettably, there was no statistical significance after multivariate analysis. Moreover, consistent with prior studies [27,28], we also demonstrated an independent association between left ventricular aneurysm and LVT. Interestingly, sixteen patients were diagnosed with ventricular aneurysm, 93.75% (15/16) of whom had LVT.…”
Section: Discussionsupporting
confidence: 92%
“…We downloaded gene expression profiles from the Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/) (16) to analyze genetic differences between DM and DMCHD. We extracted the data set from the human whole blood gene expression profile of GSE34198 based on GPL6947 (17), which included 33 healthy control samples, 34 CHD samples, 15 DM samples and 15 DMCHD samples. In GSE34198, CHD patients refers to patients who eventually develop acute myocardial infarction and DM refers to type 2 diabetes.…”
Section: Data Processingmentioning
confidence: 99%
“…Left ventricular thrombi are generally a complication associated with anterior ST-elevation myocardial infarction, dilated cardiomyopathies, or LV aneurysms. 25 -27 Dimensions, shape, grade of homogeneity, and motility of LV thrombi are all characteristics defining the embolic risk and addressing the therapeutic management. 7…”
Section: Discussionmentioning
confidence: 99%